Primary arthroplasty as an option for surgical treatment of unstable intertrochanteric fracture femur in elderly patients: a retrospective study - Kanchan, Shashank; Raj, Vikash; Agarwal, Dinesh; ., Richa (International Journal of Research in Orthopaedics, 2019)
Background: An unstable intertrochanteric fracture in osteoporotic elderly patients presents a very challenging problem to the surgeons. This category of patients if kept in bed for long tends to have many complications like deep vein thrombosis, pneumonia, bed sores, etc. Surgeon’s worldwide face difficulty in getting a good anatomical reduction and do not allow early mobility to these patients because of risk of loss of reduction and implant cut out. The purpose of our study is to study the usefulness of arthroplasty in these patients in terms of better functional outcomes and no increase in complication rates. Methods: It was a retrospective study involving 25 patients (17 females, 8 males) with mean age of 76±2.3 years having intertrochanteric femur fractures (AO type A 2.2 and above) with osteoporosis operated upon with bipolar hemiarthroplasty at IQ City Medical College and NM Hospital between January 2015 and January 2017. Results: All the patients were followed up for a period of 1 year. We had a mean operative time of 75 min (range 55-125 min) with an average blood loss of 450 ml. 4 of our patients required postoperative blood transfusion. All patients walked on 2nd postoperative day. We had a mean Harris hip score of 82 and mean VAS of 1 at the end of 1 year. Conclusions: Hemiarthroplasty done in cases of unstable intertrochanteric femur fractures in elderly patients with osteoporotic bones allows early weight bearing thus improves the final functional outcomes. Further randomized trials are required before deriving any conclusions.